Pengaruh Brand Ambassador dan Iklan Media Sosial terhadap Minat Beli pada E-commerce Shopee - Syapira, Riska; Hidayat, Rahmat (Forum Kerjasama Pendidikan Tinggi, 2024)
This study aims to examine the effect of brand ambassadors and social media advertising on buying interest in E-commerce Shopee. The research method used is quantitative research method with a descriptive verification approach with a questionnaire distributed to respondents who have criteria determined by the researcher. The population studied was all consumers of E-commerce Shopee users located throughout STM Hilir District, totaling 286 people. In this study, the analysis method used was multiple linear regression tests, validity and reliability tests, hypothesis testing using the Statistical Package for the Social Sciences (SPSS). The results stated that the research instruments used were proven to be valid and reliable. The results of the analysis show that the variables Brand ambassador and social media advertising significantly affect buying interest with social media advertising having a stronger influence. This is evidenced by the results of the Partial Test (T) which shows that the Brand ambassador variable has a significant value of 0.033 <0.05 and t count 2.148> t table (1.650), so there is a positive and significant influence between the Brand ambassador variable on consumer buying interest variables and the social media advertising variable has a significant value of 0.001 <0.05 and t count 10.444> t table 1.650, so there is a positive and significant influence between social media advertising variables on consumer buying interest variables. The coefficient of determination (R2) indicates that the variation in purchase intention can be explained by both variables.